Electromagnetic wave absorbing properties of coconut shell-derived nanocomposite. (30th August 2022) - Yang, Shuang; Sun, Xianxian; Wang, Shasha; Ning, Yuanhao; Yuan, Ye; Yin, Weilong; Li, Yibin
Abstract: Lightweight and low-cost carbon material have recently been considered as a promising microwave absorbing material (MAM), especially, biomass-derived carbon with diverse porous structures has attracted a lot of attention, because they are sustainable and easily modifiable. The excellent electrical conductivity of carbon material facilitates the attenuation of microwaves. At the same time, the application of a single carbon material can lead to a dramatic increase in interfacial reflection of microwave. Therefore, the carbon materials need to be modified or assembled into specific structures. Here, the coconut shell, a common biomass from agricultural by-product, is combined with magnetic material to form a high-quality microwave-absorbing nanocomposite. The coconut shell-derived nanocomposite possesses a hierarchical structure, in which the carbon matrix is laminated in sheets, with square magnetic Fe/Fe3 C cubes evenly distributed on the surface of the carbon matrix. The minimum reflection loss (RLmin ) of the nanocomposite reaches −48.87 dB at 2 mm in 16.40 GHz, and the widest effective absorption bandwidth (EAB) could be up to 7.94 GHz (from 10.06 to 18.00 GHz). The superior microwave absorption of the nanocomposite is stemmed from the synergy of dielectric-magnetic effect and enhanced interfacial polarization. This novel carbon-based composite is expected to hold great promise for practical applications in microwave absorption. Graphical abstract: Image 1